HIPERPLASIA CISTICA E INFILTRATIVA DA MUCOSA GASTRICA ASSOCIADA A ANASTOMOSE GASTROENTERICA PREGRESSA - De Franco, M. F.; Quevedo, F. C.; Vannucchi, H. (My University, 1974)
This report of a 51 yr old man documents a cystic and infiltrative epithelial gastric hyperplasia observed in the remaining gastric body, 12 yr after Billroth II gastrectomy for 'peptic ulcer'. The lesion was characterized by benign cystic glandular hyperplasia of the mucosa, muscularis mucosae and underlying submucosa. In similar cases reported in the literature, the lesion is considered by some authors as a postinflammatory and reactive process (gastric cystica) and, by others, as a congenital pathology (heterotopic malformation, diffuse congenital cystic hyperplasia, cystic and infiltrative epithelial hyperplasia). Symptoms and/or X ray findings of the lesion suggest gastric malignant tumor, but morphologic features and follow up indicate its benign nature.
Cystic and infiltrative epithelial gastric hyperplasia at gastroenterostomy site